Changes in antidepressant medication use in the workplace and sustainable employability: a qualitative study of experiences, strategies and solutions. Issue 1 (27th January 2022) - Hansen, Vibeke; Pit, Sabrina Winona; Fiorentino, Michele; Campion, Selina; Abraham, Ryan; Cheng, Jonathan; Phelan, Sue
Abstract: This study explores patients' experiences of how antidepressant medication transition events (ceasing, changing or reducing) affect employment and workplace functioning. An anonymous online survey was conducted with adults who had experienced antidepressant medication transition events (AMTEs). Data were analyzed using a hybrid inductive and deductive thematic analysis approach. While a majority of participants perceived many positive impacts of antidepressant medication on their workplace functioning, considerable negative effects during AMTEs were reported. Participants provided practical solutions to assist employers, policy and clinicians. Significant and detrimental impact of antidepressant medication changes occurred in the workplace. There is an urgent need to raise awareness of the vulnerability of people during AMTEs and to develop educational and supportive resources to assist clinicians and practitioners to support people during this vulnerable time.